Organization of Research Activities at University Department: Management Mechanisms for “Uncontrollable” Scientists - S. D. Reznik; O. A. Sazykina (Высшее образование в России)
The purpose of the article is to assess the level of involvement of faculty, postgraduate students and students in research work of department and to suggest mechanisms for enhancing their participation in research on the basis of monitoring the activities of heads of departments. Methodical approaches. The object of the study were 350 heads of departments of 24 higher educational institutions in different regions of Russia. Subject of research – the level of involvement of faculty, postgraduate students and students in the research work of university departments. For monitoring, a special questionnaire was proposed to the department heads. Results. The results of the monitoring of the organization of research work in Russian universities have shown that over the past ten years, the research activities of faculty, postgraduate students and students have increased significantly. This is evidenced by the growing number of departments whose faculty regularly engage in research work. Their number currently stands at 79,1% (in 2003 there were only 67,9% of such departments). The interviewed heads of departments noted that the main forms of faculty research are: the publication of scientific articles (92,3%), the publication of monographs (72,3%), participation in research (70,0%), preparation of applications for participation in grants and program competitions (62,6%). However, among the negative aspects of the organization of research work at the departments, the fact should be noted that 45,6% of the surveyed department heads hardly find time for research work with students, and 3,6% do not conduct any research with students at all. The mechanisms of activating the involvement of faculty, postgraduate students and students in the effective research work of the department are proposed, such as: the organization of scientific seminars for faculty; postgraduate seminars (Schools of young scientists for postgraduate students, as well as for master’s and undergraduate students within the framework of student self-government structures); increased participation of faculty in grant competitions and in contracting with enterprises; increasing of faculty publication activity due to the preparation of monographs and scientific articles and participation in scientific conferences; intensification of students’ research work (scientific circles, participation in contests and conferences, publications). The use of the proposed mechanisms for managing the research work of the department will help to enhance the publication activity of faculty, encourage the development of extracurricular work with students; increase the number of grants won and research conducted.